The effect of cooling prior to and during exercise on exercise performance and capacity in the heat: a meta-analysis - Tyler, C. J.; Sunderland, C.; Cheung, S. S. (British Journal of Sports Medicine, 2015)
Exercise is impaired in hot, compared with moderate, conditions. The development of hyperthermia is strongly linked to the impairment and as a result various strategies have been investigated to combat this condition. This meta-analysis focused on the most popular strategy: cooling. Precooling has received the most attention but recently cooling applied during the bout of exercise has been investigated and both were reviewed. We conducted a literature search and retrieved 28 articles which investigated the effect of cooling administered either prior to (n=23) or during (n=5) an exercise test in hot (wet bulb globe temperature >26°C) conditions. Mean and weighted effect size (Cohen's d) were calculated. Overall, precooling has a moderate (d=0.73) effect on subsequent performance but the magnitude of the effect is dependent on the nature of the test. Sprint performance is impaired (d=-0.26) but intermittent performance and prolonged exercise are both improved following cooling (d=0.47 and d=1.91, respectively). Cooling during exercise has a positive effect on performance and capacity (d=0.76). Improvements were observed in studies with and without cooling-induced physiological alterations, and the literature supports the suggestion of a dose-response relationship among cooling, thermal strain and improvements in performance and capacity. In summary, precooling can improve subsequent intermittent and prolonged exercise performance and capacity in a hot environment but sprint performance is impaired. Cooling during exercise also has a positive effect on exercise performance and capacity in a hot environment.